2015
DOI: 10.1111/ajgw.12162
|View full text |Cite
|
Sign up to set email alerts
|

Root-zone management practices impact above and belowground growth in Cabernet Franc grapevines

Abstract: Background and Aims The objective of this study was to assess the effect of root pruning (RP) and annual under‐trellis cover crops (UTCC) on vegetative growth and physiological processes in Cabernet Franc (Vitis vinifera L.) grapevines grafted on 3309C rootstock. Methods and Results Five root‐zone management treatments, namely under‐trellis vegetation‐free strip control (C), RP and three distinct annual UTCC [annual ryegrass (AR), buckwheat, (BW) and turnip (TP)] were evaluated and compared over three seasons … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 47 publications
6
22
0
Order By: Relevance
“…Competition for water was insufficient in this study to affect growth because midday stem water potential was consistently above growth-inhibiting values of -0.9 to -1.2 MPa (Girona et al, 2006;Schultz and Matthews, 1988). The water potentials in this study were similar to previously reported values for wine grape vines in the Finger Lakes region (Centinari et al, 2015;Intrigliolo et al, 2009). The predawn stem water potential values were never lower than -0.3 MPa, suggesting that the plants rehydrate at night and that water was never a growth-limiting resource.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Competition for water was insufficient in this study to affect growth because midday stem water potential was consistently above growth-inhibiting values of -0.9 to -1.2 MPa (Girona et al, 2006;Schultz and Matthews, 1988). The water potentials in this study were similar to previously reported values for wine grape vines in the Finger Lakes region (Centinari et al, 2015;Intrigliolo et al, 2009). The predawn stem water potential values were never lower than -0.3 MPa, suggesting that the plants rehydrate at night and that water was never a growth-limiting resource.…”
Section: Discussionsupporting
confidence: 89%
“…Cover crops have been found to reduce vine rooting near the soil surface and encouraged deeper rooting patterns in wine grapes (Morlat and Jacquet, 2003). 'Cabernet franc' vines in the Finger Lakes region shed fine roots growing within the root zones of BW and ARG cover crops, favoring root growth in other, less competitive parts of the soil profile (Centinari et al, 2015). In this study, the nearly 20-year-old vines in this dryfarmed 'Riesling' vineyard were likely able to overcome any competition effects from the comparatively shallow root systems of the cover crops.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…Several studies have shown that permanent swards reduce the presence of vine roots in the upper 20–30 cm of soil, and permanent swards also reduce lateral expansion towards the centre of the inter‐row (Saayman and Van Huyssteen , Van Huyssteen , Morlat and Jacquet ). Competition for water and nutrients between grass and vine is the most important factor that explains the deep colonisation of the vine roots in vineyards managed with permanent sward (Saayman and Van Huyssteen , Morlat and Jacquet , Yao et al , Lopes et al , Ruiz‐Colmenero et al , Centinari et al ). Nevertheless, the behaviour of the grapevine root system depends on the intensity and duration of cover crop competition.…”
Section: Introductionmentioning
confidence: 99%